Nda Mona . I Have Seen - Pakleppa, Richard ((n/a), 1999)
Soros Documentary Fund “Landscape of Memory” is a set of videos produced by a coalition of Southern African film-makers and covers the different ways that people have found to deal with great traumas in Namibia and South Africa. The Namibian video, “I Have Seen”, volume two of "Landscape of Memory,” is about the occupation of Namibia by South African forces and their repression of the Namibian liberation movement (SWAPO). This repression fostered fears that the movement was being betrayed from within. SWAPO's response in exile was to detain hundreds of Namibians after accusing them of being spies for Pretoria. The detainees were tortured until they died or confessed on video. The number of those who disappeared in the “operation” is yet unknown. SWAPO has never explained, apologized to, or cleared the names of the detained.